The Impact of Emotional Intelligence Training on Nurses' Performance in Providing Nursing Care in 2025 - Devi Kristina Hutagalung (International Journal of Health Sciences, 2026)
Background:Nurses' performance in providing nursing care is influenced not only by technical competence but also by non-technical skills such as emotional intelligence (EI). EI helps nurses manage emotions, communicate effectively, and make decisions that support patient safety and comfort. Objective:To assess the effect of emotional intelligence training on improving nurses' performance in providing nursing care. Method:Quasi-experimental with a one-group pretest–posttest design. The sample consisted of 60 nurses (total sampling) from three treatment rooms at Hospital X who participated in a two-day EI training with 8 weeks of follow-up practice and guidance. Instruments: (1) Emotional Intelligence Scale (valid and reliable) to measure EI; (2) Questionnaire and nurse performance checklist covering aspects of communication, assessment, intervention, documentation, and ethics. Analysis used paired t-test and multiple linear regression (α = 0.05). Results:The average EI score increased significantly from 62.8 ± 8.7 to 78.4 ± 7.9 (p < 0.001). Performance scores increased from 70.1 ± 9.2 to 84.6 ± 8.1 (p < 0.001). Increased EI was positively correlated with improved performance (r = 0.68, p < 0.001). Regression showed that changes in EI explained 46% of the variance in performance (R² = 0.46, p < 0.001) after controlling for age, tenure, and education. Conclusion:Emotional intelligence training effectively improves EI and nurses' performance in providing nursing care. Recommendation: Integrate EI training into nurse competency development programs regularly.